Vibration Exposure of Workmen of Coal Preparation Plants – An Exploratory Study. (July 2014) - Mandal, B B; Bhattacharya, S; Anupam, A; Jain, P K
22 locations in two coal preparation plants in India were evaluated in regard to their vibration characteristics and probable effects on the health of the operators and supervisors of those plants. In some cases notwithstanding the apparently sufficient isolation, vibration was found to be comparatively high. Seven hours as maximum possible exposure duration in any posture in a shift has been adopted in this study. Based on a comparative ranking DMC, vibrating screens, belt conveyors etc, in that order, pose certain health risk to the plant operators in terms of whole body vibration. The hazard potential was found to be related with the make of equipment, nature of installation, operating principles, operating practices, equipment capacity, etc. This exploratory study indicates that epidemiological studies should be conducted in large number of coal preparation plants to ascertain the nature of effects on health due to foot transmitted vibration in tropical climate, though risk assessment models from ISO Standards might not be effectively applied in such cases.